The role of the male produced pheromone in the reproduction behaviour of the southern armyworm Pseudaletia separata (Wlk.) : a thesis presented in partial fulfilment of the requirements for the degree of Master of Science in Zoology. - Clearwater, John Russell (Massey University, 1971)
Detailed courtship patterns have been described for few species of Lepidoptera. Most of the descriptive work in the literature is fragmentary or lacking in experimental or statistical analysis. Brower, Brower, and Cranston (1965) working on wild populations of the queen butterfly Danaus gilippus berenice have statistically analysed the probability of each movement in the sequence and have given a reliable and detailed account of mating in this species. Tinbergen (1958) by the presentation of models of varying size and colouration, and examining the affect of removal of structures suspected to be important in courtship has produced a good experimental account of mating in Satyrus semele the grayling butterfly. Because of the greater difficulties of observing complete mating sequences of nocturnal insects in the wild, most moth studies have been carried out with small caged populations. Again detailed expermental work is rare. The studies of Shorey (1964) on the cabbage looper Trichoplusia ni and Birch (1970) on the angleshades moth Phlogophora meticulosa possess good experimental detail suggesting that chemical cues are much more important in the courtship of moths than in butterflies. Development of more definitive techniques has allowed the investigation of insect courtship to move from subjective descriptions of the movement sequence to precise studies of the visual, tactile and chemical cues. In particular the availability of gas chromatography and mass spectrometry techniques capable of detecting the very small amounts of material produced by insects, has revolutionised the study of the chemicals, or pheromones, that are used in intra- specific communication.[FROM INTRODUCTION]
Keywords: Armyworms; Pheromones